Suppressed serological vitamin A in patients with liver cirrhosis is associated with impaired liver function and clinical detoriation. Issue 10 (21st July 2022) - Nagel, Michael; Labenz, Christian; Dobbermann, Henrike; Czauderna, Carolin; Wallscheid, Nina Cabezas; Schattenberg, Jörn M.; Wörns, Marcus A.; Galle, Peter R.; Marquardt, Jens U.
Abstract : Background: The liver is of critical importance for the homeostasis of metabolic and immunomodulatory properties as well as the storage of vitamins, especially vitamin A. In this prospective analysis, the incidence of serological vitamin A deficiency and the association with disease severity as well as clinical complications in patients with liver cirrhosis were investigated. Method: From May 2017 to May 2018, 159 patients with primarily alcohol-associated and non-alcoholic steatohepatitis (NASH)-associated preexisting liver cirrhosis were prospectively enrolled and vitamin A status was collected. Clinical complications and infections were followed and recorded over a period of 1-year follow-up. Selected findings were validated in an independent cohort of 44 patients. Results: At study inclusion, 77% of patients showed decreased serological vitamin A. Suppressed vitamin A was more common in alcoholic (52 vs. 8%) and NASH-associated liver cirrhosis (16 vs. 9%) than in viral-associated liver cirrhosis. MELD score as well as Child-Pugh score were significantly associated with suppressed vitamin A ( P  < 0.001). The association between the degree of vitamin A suppression and liver function was confirmed in univariate and multivariate regression analysis. After 1 year of follow-up, 57 patients died and 21 patients received a liver transplant. In addition, low vitamin A levels were more commonly observed in patients with severe ascites ( P  = 0.001), hepatic encephalopathy ( P  = 0.002) and hepatorenal syndromes ( P  = 0.008). In addition, patients with reduced vitamin A showed an increased incidence of infections ( P  = 0.02), especially respiratory infections ( P  = 0.04). Conclusion: Suppressed serological Vitamin A is common in patients with liver cirrhosis and is associated with liver function. Clinical complications and infections are more frequent in patients with liver cirrhosis and vitamin A suppression.